The Association Between Acceptance of Illness and Quality of Life Among Rheumatoid Arthritis Patients in Egypt - Ayad, Terivina Ayad Naguib (AUC Knowledge Fountain, 2026)
Rheumatoid arthritis is a common connective tissue autoimmune disease that has multidimensional impact on the patients’ daily functioning and quality of life. Due to the long- lasting incurable nature of RA, psychosocial adaptation to living with it becomes inevitable. Literature indicates that acceptance of illness as an appraisal of the disease and personal attitude towards it is related to better quality of life. The present study aims at investigating the relationship between disease acceptance and quality of life among rheumatoid arthritis patients in Egypt. This study also investigates the association of selected socio-demographic and disease related variables with quality of life and disease acceptance. A total of 125 patients participated in the study by answering a self-report questionnaire that included the WHOQoL-BREF and the acceptance of illness scale (AIS) as well as questions on socio-demographic and disease related data. Results indicate a positive correlation between acceptance of illness scores and the participants’ scores on all domains of quality of life. Results also highlight the educational level of participants as an important socio-demographic factor in the process of accepting and adapting to RA. Findings of this study accentuate the importance of integrating acceptance-based interventions in psychological care services for RA patients.